(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the satisfaction of inpatients at the Faculty of Traditional Medicine and Pharmacy – Saint Paul General Hospital in 2023 - 2024 Subjects and Methods: Cross-sectional descriptive study of 250 inpatients at the Faculty of Traditional Medicine and Pharmacy – Saint Paul General Hospital from March 2023 to March 2024. Results: Overall satisfaction was 93.6%. Treatment cost scored the highest satisfaction (4.91 ± 0.29); Hospital admission procedure factor lowest (4.61 ± 0.49). The average satisfaction score for the factors of facilities, medical staff and waiting time were 4.72 ± 0.53, 4.89 ± 0.29, 4.63 ± 0.38 in the order given. Conclusion: Most of the inpatients are satisfied with the quality of expertise and services when receiving inpatient treatment service at the Faculty of Traditional Medicine and Pharmacy – Saint Paul General Hospital.